Leukocyte profile in cord blood of newborns to diabetic and non-diabetic mothers - Thaseen, Nazima; Veeraiah, Shivakumar (International Journal of Research in Medical Sciences, 2021)
Background: Increasing incidence of diabetes due to strees inducing life-style, involves dearrangement of carbohydrate, fat, protein metabolism characterized by hyperglycemia, hyperlipidimia and negative nitrogen balance respectively. Causing morbidity and mortality, effects gestational diabetes. Pregnancy, capacity to secrete insulin increases with gestational age, has effect in last trimester of pregnancy. Maternal glycemic-status influences neonates leucocyte profile. Methods: Fully automated haematology analyzer ABXMICROsot used to analyze cord blood of neonates born to 40 diabetic (known to be diabetic at pregnancy) and 40 non-diabetic mothers, collected in EDTA tubes. Diabetic group was sub divided into D1 and D2. D1 as 100-150 mg/dcl, D2 as above 150 mg/dcl. Statistical treatment of Levene’s test of equality of variances applied to the data. Results: WBC count, granulocyte percent and monocyte percent were significantly lower, lymphocyte percent was higher in neonates to diabetic mothers. Significantly higher in D2 then D1group. The prognosis for the child of a pregnant diabetic is related to the degree of control of mother’s glycemic status, reflected higher indices in D2 then D1. Conclusions: Neonates immune system depends on the mother’s immune system i.e.; immunological properties are practically under control of interleukin-1 and interleukin-6. Interleukin-6 potentiates action of interleukin-1 synergistically, such action of interleukin converts non-committed stem cells to committed stem cells. Immunosuppressant status in diabetic mother (i.e.; non-priming of neonatal interleukin-6 by immunosuppressant diabetic mother’s interleukin-6, main cause for altered counts) modulating neonatal interleukin-6 it decreases haematopoietic potential in the neonates, ECF in infants of diabetic mother is reduced leading to haemo-concentration, increasing cell count. Pictures as increase cell count at birth in neonates of diabetic mother.